The effect of a new developed synbiotic yogurt consumption on metabolic syndrome components in adults with metabolic syndrome: a randomized controlled clinical trial - Mohammad-Amin Zolghadrpour; Mohammad-Reza Jowshan; Mohammad Heidari Seyedmahalleh; Farzad Karimpour; Hossein Imani; Somayyeh Asghari (Nutrition & Diabetes)
Abstract Background Studies have proposed that probiotic intake may ameliorate some of the clinical components of metabolic syndrome (MetS). This study aimed to determine the effects of a new developed synbiotic yogurt containing Lactobacillus plantarum, Lactobacillus pentosus, and Chloromyces marcosianos yeast on the components of MetS in adults with MetS. Methods In this randomized, placebo-controlled, clinical trial, 44 participants were divided into two groups to receive 300 grams of synbiotic yogurt or regular yogurt daily for 12 weeks. Anthropometric measurements, blood pressure, and biochemical parameters evaluated before and after the intervention. Results Daily consumption of synbiotic yogurt containing L. plantarum, L. pentosus, and C. marcosianos yeast in adults with MetS caused a significant decrease in the levels of fasting blood glucose (FBG) (p = 0.005), fasting insulin (p = 0.001), homeostatic model assessment for insulin resistance (HOMA-IR) index (p < 0.001), waist to hip ratio (WHR) (p = 0.02) and systolic blood pressure (p = 0.008) in the intervention group compared to the control group. Conclusions According to the findings of this study, daily consumption of the synbiotic yogurt was associated with improvements in insulin resistance, systolic blood pressure and WHR, which could be beneficial in patients with MetS.